Implementasi Kurikulum Merdeka Dalam Pembelajaran Pendidikan Agama Islam - Qolbiyah, Aini (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
This paper discusses innovations in Islamic religious education which are very basic things and need to be implemented. The policy of "Merdeka Belajar" is an idea from the Minister of Education and Culture Nadiem Makarim in order to improve the national education system. The concept of "Merdeka Belajar" is an attempt to realize independence in thinking. This research was carried out at SMK Negeri 5 Pekanbaru. The type of research is descriptive qualitative using a field study approach (field research). Methods of collecting data by means of observation, interviews and documentation. The informant of this study was a teacher of islamic religion of education. the results of the study indicate that the renewal (innovation) method used when learning Islamic religious education is to use the Contextual Teaching and Learning method or strategy (CTL). Innovative teaching materials are currently prepared by Islamic Religious Education teachers themselves. In the learning process, teachers use PowerPoint and Video.